Higher order corrections of the extended Chaplygin gas cosmology with varying $$G$$ G and $$\Lambda $$ Λ - Kahya, E.O.; Khurshudyan, M.; Pourhassan, B.; Myrzakulov, R.; Pasqua, A. (Springer Science and Business Media LLC, 2015)
In this paper, we study two different models of dark energy based on Chaplygin gas equation of state. The first model is the variable modified Chaplygin gas while the second one is the extended Chaplygin gas. Both models are considered in the framework of higher order $f(R)$ modified gravity. We also consider the case of time varying gravitational constant $G$ and $$ for both models. We investigate some cosmological parameters such as the Hubble, the deceleration and the equation of state parameters. Then we showed that the model that we considered, extended Chaplygin gas with time-dependent $G$ and $$, is consistent with the observational data. Finally we conclude with the discussion of cosmological perturbations of our model.

Perturbation analysis added, typos corrected, references added
Keywords: Physics and Astronomy (miscellaneous); FOS: Physical sciences; General Relativity and Quantum Cosmology (gr-qc); Engineering (miscellaneous); General Relativity and Quantum Cosmology